Second-generation Liquid Platelet Concentrates: A Literature Review - Shah, Rucha; Gowda, Triveni M.; Thomas, Raison; Kumar, Tarun (Current Pharmaceutical Biotechnology, 2022)
Liquid or injectable platelet-rich fibrin (PRF) is a second-generation platelet concentrate that is completely autologous and free of external additives, like bovine thrombin and calcium chloride. Additionally, it is the only one to be obtained in a liquid form among the second-generation platelet concentrates. This allows for wide applications such as maximizing injections or mixing with biomaterials such as bone grafts or antibiotics. Since it was first introduced in 2015, several modifications of the original protocol have been proposed which aim at maximizing its biological and mechanical properties. This includes changes in centrifugation speed, time, and so on. The aim of this review is to summarize the various modifications of the injectable/liquid formation of PRF as well as to discuss the potential applications and future research direction.
Keywords: leukocytes